Prevención y complicaciones de episiotomía en gestantes primigestas. Hospital Carlos Andrade Marín, 2021 - Chamorro Martínez, Gina Jessica (2022)
ABSTRACT Episiotomy is a surgical procedure performed during cephalovaginal delivery to increase the opening of the vaginal canal to facilitate the delivery of the fetus; it is frequently performed in primiparous women and in those who present risk factors for episiotomy. The objective of this research was to identify preventive measures and incidence of episiotomy complications in primigravid pregnant women at the gynecological-obstetrics service of the Hospital de Especialidades Carlos Andrade Marín, by means of a retrospective study including patients with cephalic-vaginal delivery during the year 2021, from which statistical data were obtained about the frequency of episiotomy in this health unit, main predisposing factors, incidence of complications and their severity in primiparous women. The methodology used was quantitative, descriptive explanatory in scope; the population consisted of 287 patients whose medical records were reviewed. This study shows that the most frequent complications in primiparous patients are moderate perineal pain, surgical site infection, dyspareunia, vulvar edema and to a lesser degree hematoma. We conclude that episiotomy provides maternal-fetal benefits, however, it can cause greater postpartum complications, and for this reason it is recommended that it be performed selectively. Key words: episiotomy, childbirth, complications, cephalovaginal, risk factors. Reviewed by: MsC. Edison Damian Escudero ENGLISH PROFESSOR C.C.0601890593